2012
DOI: 10.1007/s11837-011-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D Characterization of Solidification Structure and Defect Evolution in Al Alloys

Abstract: Geometrically complex, as-cast, aluminum alloy components offer substantial economic and design advantages as compared to many thermo-mechanical processing routes. However, the occurrence of potential defects, including porosity, intermetallics and hot-tears, remains an issue. Using these three defects as examples, recent developments in the methodologies for quantifying defect evolution and microstructure using 3D images captured in situ via X-ray microtomography are discussed. It is demonstrated that 3D quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…2c). 55 Such in situ work has also shown that the 2 Fast imaging acquired during a high temperature tensile test of a semi-solid aluminium alloy. In this example, fast imaging is combined with digital volume correlation and image processing bringing new insights.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…2c). 55 Such in situ work has also shown that the 2 Fast imaging acquired during a high temperature tensile test of a semi-solid aluminium alloy. In this example, fast imaging is combined with digital volume correlation and image processing bringing new insights.…”
mentioning
confidence: 96%
“…In this example, fast imaging is combined with digital volume correlation and image processing bringing new insights. 55 a A virtual section during the hot tearing of partially solidified metal, b the local variation in strain determined by digital volume correlation and c the volume change of the voids between steps, which shows the internal growth of the voids in the localised deformation region results (e.g. the variation in the measured specific surface) obtained when characterising coarsening using a standard ex situ quenching and sectioning procedure are very different to what is observed under real time in situ continuous observation of the semi-solid microstructure.…”
mentioning
confidence: 99%
“…Samples were clamped between a set of purpose-built grips and loaded onto a bespoke micro-mechanical tester (P2R) (Puncreobutr et al, 2012). Tensile deformation was performed at a rate of 0.1 mm s −1 until failure.…”
Section: In Situ Synchrotron Imaging and Tensile Deformationmentioning
confidence: 99%
“…However, compressor disks are often subjected to cold working before entering service, in order to increase resistance to fatigue [4]. This is 15 achieved by surface treatment to produce compressive residual stresses at the surface. In the past this was most commonly achieved by shot peening, where the surface of the disk is bombarded by small spherical shot with enough force to produce dimples on the component service.…”
Section: Introductionmentioning
confidence: 99%